Barriers and Facilitators of Conducting Medication Reviews in Nursing Home Residents: A Qualitative Study - Wouters, Hans; Foster, Juliet M.; Ensink, Anne; O’Donnell, Lisa Kouladjian; Zuidema, Sytse U.; Boersma, Froukje; Taxis, Katja (Frontiers in Pharmacology, 2019)
Objectives: Inappropriate medication prescribing is a recognized clinical problem in nursing home residents of whom many have polypharmacy. However, results about the effectiveness of medication reviews targeted at improving prescribing and deprescribing have been equivocal. We therefore examined barriers and facilitators of conducting medication reviews. Method: We purposively sampled medication reviews to capture salient barriers and facilitators of conducting medication reviews both in nursing home care units for dementia and disabling conditions. We held semi-structured interviews about consecutive steps of medication reviews. Interviews were transcribed verbatim and analyzed with the ‘method of constant comparison’. Results: Six nursing home residents/relatives of nursing home residents, 8 elder care physicians, 5 pharmacists, and 10 nurses took part in the semi-structured interviews. We observed 4 overarching themes of barriers and facilitators: ‘Realizing fidelity of the patient perspective (theme 1)’, ‘Level of comprehensiveness of medication reviews (theme 2)’, ‘Inclinations of healthcare providers (theme 3)’, and ‘Inter-professional collaboration and alliances’ (theme 4)’. Theme 1 ‘Realizing fidelity of the patient perspective’ referred to the observation that assessing the patient perspective was a delicate balance between the value and the impediments of a proper assessment of the patient perspective. Theme 2 ‘Level of comprehensiveness of medication reviews’ reflected the struggle of practitioners to find an optimum between medication reviews being both comprehensive and feasible. Theme 3 ‘Inclinations of healthcare providers’ concerned setting intervention targets that were complementary to the practices of physicians and keeping the pharmacist blind to the patient perspective as a countermeasure to physicians’ inclinations. Finally, theme 4 ‘Inter-professional collaboration and alliances’ highlighted mutual support and inter-professional collaboration to strengthen healthcare practitioners’ contributions. Discussion: These themes of barriers and facilitators emphasize the need to improve meta-communication during the medication review process. This pertains to the need for healthcare providers to appraise the fidelity of the patient perspective in a dialogue with residents/relatives. Furthermore, discourse between healthcare practitioners is needed beforehand about the comprehensiveness, intervention targets and inter-professional collaboration.